EXPLORING WRITING CHALLENGES IN DEAF AND HARD OF HEARING STUDENTS WITH COCHLEAR IMPLANTS: THE ROLE OF DYSGRAPHIA - Septiani, Dwi; Koebanu, Sabri; Lustyantie, Ninuk (JURNAL EDUSCIENCE, 2025)
Purpose–This study explores the writing development of Deaf and Hard of Hearing (DHH) students with cochlear implants, focusing on the impact of dysgraphia, a specific learning disability affecting writing abilities. The research aims to understand how cochlear implants influence language acquisition and writing proficiency while addressing the unique challenges posed by dysgraphia, such as difficulties in fine motor skills, sound-symbol associations, and organizational abilities.Methodology–Utilizing Piaget’s theory of cognitive development, the study employs a qualitative case study design to investigate the writing journey of a 7-year-old male DHH student suspected of having dysgraphia. Data were collected over one academic semester through document analysis of writing samples, classroom observations, and semi-structured interviews with teachers and support staff. Thematic analysis was conducted to identify patterns in the student’s cognitive and linguistic challenges, highlighting the interplay between hearing impairment, cochlear implant use, and dysgraphia.Findings–Findings reveal that while cochlear implants enhance auditory input and phonemic awareness, dysgraphia significantly hinders writing skills, manifesting in irregular letter formation, inconsistent spacing, and poor spelling. However, structured interventions, such as multisensory approaches and assistive technology, show promise in improving writing outcomes.Contribution–This research contributes to the field by providing insights into the unique challenges faced by these students and advocating for personalized interventions to enhance their literacy skills. It also highlights the need for further research to explore the prevalence of dysgraphia and effective interventions for DHH students with cochlear implants, ultimately informing inclusive educational practices.